The angiotensin II type I receptor blocker olmesartan inhibits the growth of pancreatic cancer by targeting stellate cell activities in mice. (May 2013) - Masamune, Atsushi; Hamada, Shin; Kikuta, Kazuhiro; Takikawa, Tetsuya; Miura, Shin; Nakano, Eriko; Shimosegawa, Tooru
Abstract There is accumulating evidence that pancreatic stellate cells (PSCs), a major profibrogenic cell type in the pancreas, promote the progression of pancreatic cancer. The interactions between PSCs and pancreatic cancer have attracted substantial attention as a novel therapeutic target for the treatment of pancreatic cancer. We examined here the effects of olmesartan, an angiotensin II type I receptor blocker, on pancreatic cancer-associated fibrosis using a subcutaneous tumor model developed by co-injection of pancreatic cancer cells with PSCs in nude mice. Co-injection of pancreatic cancer cells AsPC-1 with PSCs increased the size of tumors compared with AsPC-1 cells alone. Olmesartan administrated at 10 mg/kg in drinking water inhibited the growth of subcutaneous tumors derived from the co-injection, but not those derived from mono-injection. This effect was accompanied by decreased expression of α-smooth muscle actin (a marker of activated PSCs) and collagen deposition. The inhibitory effect of olmesartan was also observed even if it was administrated after significant development of subcutaneous tumors. In addition, olmesartan decreased cell growth and type I collagen production in PSCs in vitro. These results suggest that olmesartan inhibited the growth of tumors by targeting stellate cell activities, and that olmesartan might be useful as an anti-fibrosis therapy in pancreatic cancer.